Endoluminal thermal ablation of the great saphenous vein (GSV) insufficiency - Sporbert, F.; Zollmann, C.; Zollmann, P.; Veltman, J.; Gräser, A.; Berger, I.; Rabe, E. (Phlebologie, 2016)
To evaluate and compare the fiveyear outcome after treatment of a varicose GSV by endovenous thermal laser ablation (EVLA) and radiofrequency ablation (RFA).In this non-randomized, prospective study, patients treated in 2007 and 2008 for complete varicosis of the GSV (CEAP: C2–C6) were divided according to the treatment technique used into three groups: RFA (VNUS ClosureFast™), EVLA 980 nm (ELVeS 980™) and EVLA 1470 nm (ELVeS 1470™). Ultrasound-guided follow-up consultations were conducted 3 days, 3 months, 1 year and 5 years after treatment.589 patients with 643 GSVs (223 RFA, 185 EVLA 980, 235 EVLA 1470) were treated under tumescent local anaesthesia. No major complications occurred and minor complications were rare (4.7–12.2 %, p=0.135).66 % (RFA), 15 % (EVLA 980) and 32 % (EVLA 1470) of the patients were pain-free without post-operative analgesics. After 5 years, 86 % (RFA), 90 % (EVLA 980) and 93 % (EVLA 1470) of the veins were occluded (p=0.096). Ultrasound imaging revealed reflux in treated GSVs in 5–8 % of cases (p=0.73). A second ablation of the previously treated GSV was required in 5 % (RFA), 2 % (EVLA 980) and 2 % (EVLA 1470) of the patients (p=0.28).Endoluminal thermal ablation is an easy, safe and well tolerated method for the treatment of varicosis. Radiofrequency ablation is less painful than EVLA. RFA and EVLA 1470 are equally effective for vein closure.
Keywords: Great saphenous vein (GSV); endovenous thermal laser ablation (EVLA); radiofrequency ablation (RFA); varicose veins